Kesetaraan Gender dalam Hukum Keluarga Islam dan Hukum Positif - Wani Wani; Faisar Ananda Arfa; Ibnu Radwan Siddiq Turnip (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This paper discusses the issue of gender equality from the perspective of Islamic family law and positive law in Indonesia. This study begins with a historical exploration of the treatment of women in the pre-Islamic era which was full of discrimination and oppression, until the arrival of Islam which brought about a major transformation towards respecting and recognizing women's rights. Furthermore, this paper reviews the comparison between the values ​​of gender equality in ideal Islamic family law with practices that are still influenced by patriarchal culture, as well as Indonesia's positive legal response to gender issues, such as through the Compilation of Islamic Law (KHI), the Marriage Law, and the ratification of international conventions such as CEDAW. This study also highlights the role and existence of women in the family as children, wives, and mothers, as well as the challenges faced by women in fighting for rights and equality in the domestic and public spheres. This paper emphasizes that achieving fair and balanced gender equality requires a reinterpretation of the law based on values ​​of justice and a structural commitment to empowering women in all aspects of life.